Establishment of reference audiometric norms for the elderly population: A community-based study on mean and median hearing thresholds - Tzong-Hann Yang; Yu-Fu Chen; Yen-Fu Cheng; Chuan-Song Wu; Yuan-Chia Chu (Heliyon)
Background: This investigation quantifies the mean and median hearing thresholds and assesses the prevalence of age-related hearing loss within the senior population of Taipei. Methods: In a substantive geriatric assessment supported by government initiative, 1696 individuals from a community hospital partook in this cross-sectional study (2016–2018). Detailed audiometric evaluations logged pure-tone thresholds across critical frequencies (0.5k, 1k, 2k, 4k Hz), in conjunction with participant ages, genders, and HHIE-S questionnaire results. Results: The findings indicated mean and median pure tone averages (PTA) of 25.3 ± 15.6 dB HL and 22.5 dB HL, respectively. Gender-based analysis showcased higher PTAs for males than females. The study illuminated a progressive increase in hearing thresholds with age and higher frequencies. A 41 % prevalence of hearing impairment was recorded, with a notable 15.2 % deemed disabling, and a potential candidacy for cochlear implantation in 1.5 % of the study group. Conclusions: Hearing loss was prevalent in 41 % of the non-hospitalized elderly demographic, chiefly characterized as mild. However, older age groups, particularly those over 85, presented an elevated occurrence of moderate hearing loss.